Detection of presence marks in stegocontent - Chia Meng, Sia (2013)
Steganography is an art of hiding message by embedding message within other types of media for example text, audio or image files. The main purpose of Steganography is attempts to hide the existence of communication. For steganography, the users totally do not want to let anyone know they are sending messages. The objectives of this project are study current steganography tools and the methods used for detection of presence marks in stegocontent, develop steganalysis tools which implement with graphical user interface (GUI), and verify and detect the marks in stegocontent in image files to assist investigation process. Peak Signal-to-Noise Ratio (PSNR) steganalysis is chose as the method used in this application software because it is use for detect various Least Significant Bits (LSB) modification techniques. LSB is the method that most commonly used in steganography to hide message.